2013
DOI: 10.1016/j.jcmg.2013.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Libman-Sacks Endocarditis and Embolic Cerebrovascular Disease

Abstract: Objective To determine whether Libman-Sacks endocarditis is a pathogenic factor for cerebrovascular disease (CVD) in systemic lupus erythematosus (SLE). Background A cardioembolic pathogenesis of SLE CVD manifested as 1) neuropsychiatric SLE (NPSLE) including stroke and transient ischemic attacks (TIA), 2) neurocognitive dysfunction, and 3) MRI focal brain lesions has not been established. Methods A 6-year study of 30 patients with acute NPSLE (27 women, age 38±12 years), 46 age-and-sex matched SLE control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 44 publications
4
105
0
2
Order By: Relevance
“…The results of that study in 102 subjects (76 SLE patients and 26 healthy controls) using 2D-TEE have been published (8). All participants provided informed consent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of that study in 102 subjects (76 SLE patients and 26 healthy controls) using 2D-TEE have been published (8). All participants provided informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, accurate detection of Libman-Sacks endocarditis may lead to early therapy and prevention of the development or progression of its associated complications. Multiplane two-dimensional (2-D) transesophageal echocardiography (TEE) has high diagnostic value for detection of Libman-Sacks endocarditis (5,6,8,12). Three-dimensional TEE (3D-TEE) has emerged as an important complementary technique to 2D-TEE for detection and characterization of infective vegetations and valve tumors (1316).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the lesions in infective endocarditis, NBTE vegetations are more friable and prone to systemic embolization. 7 NBTE is most notably associated with malignancy, antiphospholipid syndrome and SLE. 8,9 A large echocardiographic study revealed NBTE to be found in 19% of disseminated adenocarcinomas.…”
Section: Pathogenesismentioning
confidence: 99%
“…Unauthorized reproduction of this article is prohibited. 7 Clinical manifestations of embolization include focal neurological deficits, vision changes, memory loss, painful extremities, acute abdomen and flank pain.…”
Section: Pathogenesismentioning
confidence: 99%
“…7 Although it characteristically has negligible hemodynamic significance, when present, it is strongly associated with cerebrovascular and peripheral arterial embolism, cognitive dysfunction, acute and chronic valvular dysfunction, superimposed infective endocarditis, and the need for high-risk valvular surgery. 2,8,9 There is scant literature regarding the diagnostic and treatment dilemma providers face when valve perforation occurs in the setting of LS endocarditis. We conducted a systematic review of the literature on valve perforation caused by LS endocarditis, in which we performed a PubMed query with the keywords BLibman Sacks^and Bperforation^as well as BLibman Sacks^and Brepair.^Abstracts were reviewed and relevant papers were selected.…”
Section: Discussionmentioning
confidence: 99%